Is Tax Avoidance Associated with Economically Significant Rent Extraction among U.S. Firms? - Blaylock, Bradley S. (Contemporary Accounting Research, 2016)
Abstract Two influential papers in the tax‐avoidance literature (Desai and Dharmapala ; Desai, Dyck, and Zingales ) argue that aggressive forms of tax avoidance employ technologies that complement managerial rent extraction, and provide supporting evidence from firms in Russia. Several papers rely on this theory to motivate and interpret tests in a U.S. setting, but these tests are open to multiple interpretations. This paper investigates the extent to which shareholders of U.S. companies are affected by any such rent extraction. The evidence is inconsistent with the tax‐avoidance technologies employed by U.S. firms allowing managers to extract sufficient rents to negatively affect future performance. Additional tests on poorly governed U.S. firms find no evidence that tax‐avoidance activities relate positively to either overinvestment or higher executive compensation, and no evidence that either complexity or the Sarbanes‐Oxley Act moderates the relation between future performance and tax avoidance. The evidence suggests that caution is warranted in interpreting evidence according to this theory in a U.S. setting.